PENGARUH KOMITMEN PROFESI, KECERDASAN EMOSIONAL DAN PERENCANAAN KARIR TERHADAP KINERJA PEGAWAI DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DAERAH KABUPATEN LABUHANBATU SELATAN - Janra Mei Wandi Saragih; Husin .; Martina Silaban; Lamsah Saragih; Widi Hastuti (Universitas Islam Sumatera Utara, 2020)
The problems in research what is influence of profession commitment on performance. What is influence of emotional intellegence on performance. What is influence of career planning on performance. What is influence of profession commitment, emotional intellegence and career planning on performance. The research of purposes is for know and analysis influence of profession commitment on performance. For know and analysis influence of emotional intellegence on performance. For know and analysis influence of career planning on performance. For know and analysis influence of profession commitment, emotional intellegence and career planning on performance. Samples in the research amount to 52 employees people. Data analyze technique in the research using descriptive analyze and regression analize. The results of this research explain of profession commitment variable effect significant and positive on performance. Emotional intellegence variable effect significant and positive on performance. Career planning variable effect significant and positive on performance. Profession commitment, emotional intellegence and career planning variable effect significant and positive on performance.